Cosmogenic 26Al/10Be surface production ratio in Greenland. Issue 3 (2nd February 2017) - Corbett, Lee B.; Bierman, Paul R.; Rood, Dylan H.; Caffee, Marc W.; Lifton, Nathaniel A.; Woodruff, Thomas E.
Abstract: The assumed value for the cosmogenic 26 Al/ 10 Be surface production rate ratio in quartz is an important parameter for studies investigating the burial or subaerial erosion of long‐lived surfaces and sediments. Recent models and data suggest that the production ratio is spatially variable and may be greater than originally thought. Here we present measured 26 Al/ 10 Be ratios for 24 continuously exposed bedrock and boulder surfaces spanning 61–77°N in Greenland. Empirical measurements, such as ours, include nuclides produced predominately by neutron‐induced spallation with percent‐level contributions by muon interactions. The slope of a York regression line fit to our data is 7.3 ± 0.3 (1 σ ), suggesting that the 26 Al/ 10 Be surface production ratio exceeds the commonly used value of 6.75, at least in the Arctic. A higher 26 Al/ 10 Be production ratio has implications for multinuclide cosmogenic isotope studies because it results in greater modeled burial durations and erosion rates. Key Points: The cosmogenic 26 Al/ 10 Be production ratio in quartz is higher than traditionally thought and likely varies with latitude/altitude Using continually exposed rock surfaces in Greenland, we constrain the high‐latitude 26 Al/ 10 Be production ratio to 7.3 ± 0.3 A higher assumed 26 Al/ 10 Be production ratio results in greater modeled burial durations and erosion rates